Pengaruh Kecerdasan Spiritual Dan Perilaku Etis Terhadap Komitmen Organisasional Pada PT. Pegadaian Persero Cp Karombasan – Manado - Sumual, Shysilia Rennarda; Runtuwene, Roy F.; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to examine the Effect of Spiritual Intelligence and Ethical Behavior on Organizational Commitment at PT. Pegadaian Persero CP Karombasan - Manado. The population in this study were employees of PT. Pegadaian Persero CP Karombasan - Manado. The study sample used Genuine Sampling, the data sources were primary and secondary. The data analysis technique used is validity test, normality test, reliability test, multiple linear regression analysis, and coefficient of determination analysis, t test hypothesis and F test. The results of this study indicate that partially (t test) spiritual intelligence has a significant effect on organizational commitment with it is known that the value of t count is greater than t table. Ethical behavior does not significantly influence organizational commitment with the value of t calculated less than the value of t table. Based on the results of the F test it can be concluded that spiritual intelligence and ethical behavior have a significant effect on organizational commitment, this can be seen from the calculated F value greater than F table.